Women in the Polish Industry — Employment Numbers and Structure in the Years 1945-1956 - Chumiński, Jędrzej (Studia Historiae Oeconomicae, 2019)
The first decade of the Polish People’s Republic (PPR) saw a radical increase in the number of workers employed in the industry. Many of the new workers were women, whose situation on the job market was much more dynamic than men’s. New staff was mainly recruited from the rural population. Workers were poorly educated and had little work experience, which begs a question regarding the economic rationale behind this process. Some of the new employees could actually be included in the category of “hidden unemployment”. Their marginal productivity equaled zero, which means that their work had no actual impact on the gross national income. Furthermore, such “unemployment at work” negatively impacts morale and work quality, leads to increased staff turnover, and essentially prevents workers from improving their financial situation. Considering the poorer socio-demographic characteristics of women compared to men, one can pose the thesis that the rate of needless employment was significantly higher among women than among men.